Learning Outcomesʹ Assessment in Virtual Classrooms - DINCĂ, Melinda (2022)
The Learning Outcomes’ Assessment in Virtual Classrooms is an open educationalresource (OER) consisting of a systematic literature review about the learning outcomesassessment practices, methods, and tools in virtual education environment. The book isbased on more than 150 scientific articles and books, with a half being published in the last5 years (2018-2022), presenting theories, reviews meta-analysis, empirical research results,recent developments and practical experiences of online assessment approaches in thelearning process of virtual classrooms. The first chapter approaches the differences andsimilarities between HE learning settings with various degrees of virtually components;methods and practices of learning outcomes’ assessment. The second chapter identifiesinnovative practices and methods from complementary perspectives of teachers, selfreflectiveand peer-reflective assessment of the development of transversal competencies.The third chapter follows the constructivist approach and presents models of authenticlearning designs, the role and impact of the practical dimension of bringing real-life casesin the learning process of higher education students.